A Comparison of the Locus of Control, Unreasonable Beliefs and Religious Orientation in Divorce and Ordinary Women in Ardabil in 2016 - Esmaeil Sadri Damirchi; Arezoo Mojarrad; Masoomeh Pirgholi Kivi (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Family is the core of every society and the center of mental health and care satisfying the emotional, physical and spiritual needs of its members. Various factors can sustain this foundation. Some of these factors include probably the locus of control, irrational beliefs, and religious orientation. On this basis, the purpose of the present study was to compare the locus of control, irrational beliefs and religious orientation divorced women in Ardabil in 2016. Methods: The study was descriptive and causal-comparative. The statistical population included all women asking for divorce, who referred to the Ardabil Justice in 2016. The sample population included 50 women applying for divorce and 50 normal women selected based on available sampling method. The participants completed the Rutter Control Questionnaire, Jones's irrational beliefs and Alport's religious orientation questionnaire. The obtained data were analyzed using multivariate analysis of variance. All ethical considerations have been observed in the present study and the authors of the article reported no conflict of interest. Results: The results of analysis of variance showed that there was a significant difference between the women applying for divorce and normal women in the control variables (p<0.001), religious orientation (p<0.001), irrational beliefs (p<0.003), and its components including emotional irresponsibility (P<0.001), problem avoidance (p<0.001), expectation of approval from others (p<0.001), and helplessness against change (p<0.001). Conclusion: The results were indicative of a significant difference between women seeking divorce and normal women in variables of locus of control, irrational beliefs and religious orientation. Therefore, it is suggested that educational programs and workshops be organized to reduce divorces in women in order to properly manage the locus of control, irrational beliefs, and religious orientation. For downloading the full-text of this article please click here. Please cite this article as: Sadri Damirchi E, Mojarrad A, Pirgholi Kivi M. A Comparison of the Locus of Control, Unreasonable Beliefs and Religious Orientation in Divorce and Ordinary Women in Ardabil in 2016. Pizhūhish dar dīn va salāmat. 2020; 5(4):73-87. https://doi.org/10.22037/jrrh.v5i4.17138